Age of extremes : the short twentieth century 1914-1991 - Hobsbawm, E. J. (Eric John), 1917-2012 (London : Joseph, 1995)
Part 1 The age of catastrophe: total wars; the world revolution; into the economic abyss; the fall of liberalism; against the common enemy - the 1930s and 1940s; the arts 1914-45; the end of empires. Part 2 The golden age: the Cold War; the golden years; social revolution; cultural revolution; the Third World; real socialism. Part 3 The landslide: the crisis decades; the Third World and revolution; the fall of socialism; the avant-garde dies; sorcerers and apprentices - science; a millennium dies.
Hobsbawm has written a history based on his wide personal experience - he was born in the year of the Russian revolution and was in Berlin when Hitler was appointed Chancellor - and from the point of view of a believer in reason, science and the potential improvement of the human situation.
Keywords: History, Modern -- 20th century